Social and economic decision-making in Urbach-Wiethe Disease - Fourie, Jorique (Department of Psychiatry and Mental Health, 2020)
Background: Rodent and primate research have identified the basolateral amygdala as indispensable for social decision-making. This finding has not yet been translated to humans, and has even been partially contradicted by previous findings in patients with amygdala lesions that show generous economic investments in strangers. This thesis therefore aimed to determine whether selective basolateral amygdala damage in humans, caused by Urbach-Wiethe Disease, impairs instrumental non-social economic decision-making. Methods: Using an adapted reinforcement-learning task, the performance of basolateral amygdala damaged individuals (n=6) was compared with that of healthy controls (n=20) on social and economic decision-making during a probabilistic reinforcement task. The task required participants to make decisions for themselves and others based on learned probability of monetary reward or loss. A random effects Generalised Least Squares regression was conducted using Stata 15.1. to assess discrimination between Gain and Loss domains. A social-decision making task was also administered. Results: When making choices for themselves, Urbach-Wiethe Disease participants showed no difference in correct choices made between Gain and Loss domains. The Urbach-Wiethe disease participant's lack of discrimination between gains and losses for themselves was significantly different (p< 0.01) from that of controls, who made significantly more correct choices for themselves in the gain domain compared to the Loss domain. Social decision-making performance did not, however, differ significantly between Urbach-Wiethe Disease participants and controls. Conclusions: These findings regarding non-social decision-making support the important role of the basolateral amygdala as a salience detector, with lesions to this region resulting in reduced bias to the valence of potential economic outcomes, regardless of whether these pertain to costs or benefits. These findings are also consistent with prior work indicating that lesions to the basolateral amygdala can possibly produce loss-aversion due to a hypervigilance for fear and the lack of inhibition of the centromedial amygdala by the basolateral amygdala.